Infectious Clones of Tomato Chlorosis Virus: Toward Increasing Efficiency by Introducing the Hepatitis Delta Virus Ribozyme - Navas-Hermosilla, Elisa; Fiallo-Olivé, Elvira; Navas-Castillo, Jesús (Frontiers in Microbiology, 2021)
Tomato chlorosis virus (ToCV) is an emergent plant pathogen that causes a yellow leaf disorder in tomato and other solanaceous crops. ToCV is a positive-sense, single stranded (ss)RNA bipartite virus with long and flexuous virions belonging to the genus Crininivirus (family Closteroviridae). ToCV is phloem-limited, transmissible by whiteflies and it causes symptoms of interveinal chlorosis, bronzing and necrosis in the lower leaves of tomato accompanied by vigor decline and fruit yield reduction. The availability of virus infectious clones is a valuable tool for reverse genetic studies that has been long time hampered in the case of closterovirids due to their genome size and complexity. Here, the infectivity of the available cDNA ToCV agroinfectious clones (isolate AT80/99-IC from Spain) have been tried to be improved by adding the hepatitis delta virus (HDV) ribozyme fused to the 3′ end of both genome components, RNA1 and RNA2. The inclusion of the ribozyme has shown to generate viral progeny with RNA1 3’ ends more similar to that present in the clone used for agroinoculation. Nevertheless, the obtained clones were not able to infect tomato plants by direct agroinoculation, as it happens to the starting clones. However, the infectivity of the clones carrying the HDV ribozyme in Nicotiana benthamiana plants experienced, in average, a two-fold increase as compared with the previously available clones.